Study on the Physical Quality of Complete Rabbit Feed Pellets Using Different Forage Protein Sources - T. A. Y. Foenay; T. N. I. Koni (Universitas Bengkulu, 2021)
This study evaluated the physical quality of complete rabbit feed containing different legumes. The study design was an experimental method using a Completely Randomized Design with four treatments and five replications. The treatments were as follows: P1 =complete feed without legume;P2 = complete feed with 10% moringa leaves meal; P3 = complete feed with 10% Leucaena leaves meal; P4 = complete feed with 10% turi leaves meal. Parameters measured were hardness, durability, density and specific gravity of rabbit pellet complete feed. Data analysis uses analysis of variance and if there is a treatment with a significant effect, then it is continued with Duncan's multiple distance test. The results showed that legumes had no significant effect on impact resistance, friction resistance, pile density, and specific gravity of the rabbit pellets produced. It was concluded that the use of legumes, namely Moringa, lamtoro and turi did not reduce the physical quality of the pellets.